2015
DOI: 10.4103/2008-7802.161074
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of skin cancer and its trend in Iran

Abstract: Background:One of the most common cancers is skin cancer worldwide. Since incidence and cost of treatment of the cancer are increasing, it is necessary to further investigate to prevent and control this disease. This study aimed to determine skin cancer trend and epidemiology in Iran.Methods:This study was done based on existing data. Data used in this study were obtained from a national registry of cancer cases and the Disease Management Center of Ministry of Health in Iran. All cases registered in the countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 25 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…The trend of skin cancer incidence in men was increasing; on an average, it grew by 7.06% yearly. In women, this rate also raised from 12.01 in 2004 to 15.77 in 2008 per 100 000 persons (13,14).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The trend of skin cancer incidence in men was increasing; on an average, it grew by 7.06% yearly. In women, this rate also raised from 12.01 in 2004 to 15.77 in 2008 per 100 000 persons (13,14).…”
Section: Discussionmentioning
confidence: 93%
“…2018; 9(2):e82743. and Hamadan provinces (13,17,18,20). Out of the total population studied, the mean age of patients with skin cancer was 65 year that in 67% age ranged from 60 to 70 years.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Among men, the ASR (per 100,000) increased from 0.8 in the previous survey (1988–1992) to 3.8 in the current registry survey (1998–2002), and in women, this increase was from 0.7 to 2.5 per 100,000 (Masoompour et al, 2011). A study of the overall rate of skin cancer in all 30 provinces in Iran reported a male to female ratio of ~1.6–~1.7 for all skin cancers combined, but did not analyze rates separately for melanoma (Razi et al, 2015). Our comparisons of sex-specific incidence rates also depict a pattern of lower overall rates of melanoma among women in Iran.…”
Section: Discussionmentioning
confidence: 99%